Industrial Activity in the Socio-Spatial Configuration of the Yungay Neighborhood, 1930-1950 [la Actividad Industrial en la Configuración Socioespacial del Barrio Yungay, 1930-1950] - Venegas-Valdebenito, H; Prudant-Soto, E (Universidad de Chile, Instituto de la Vivienda, 2021)
The text analyzes the impact of industrial activity in the socio-spatial configuration of the Yungay neighborhood during a period of urban regulation, expansion of manufacturing, and state incentives for production. As a result of the relationship between the actors of industrialization and the dynamics of the conformation of a worker-factory environment in the northeast region of Santiago, three variables will be explored in-depth: the location of a manufacturing network that acted as a marker of the neighborhood space; the business initiatives with respect to urban infrastructure and services in this part of the city; and the sense of belonging among the population that inhabited the neighborhood in their double condition of workers and residents. The methodology located at the crossover between urban history and the history of the world of work incorporates a relational approach to identify, in the physical and representational organization of the place analyzed, a weaving of ties to the historical context that frames the 1930s and 1950s. The research results, by deepening the repercussions of industrial activity in a neighborhood little studied from this perspective, contribute to strengthening studies of factory zoning in Santiago and integrating the spatial variable in the analysis of the origins of industrialization in the Chilean capital. © 2021, Universidad de Chile, Instituto de la Vivienda. All rights reserved.